Evaluation of the Suitability of the Fishery Reserve (Reservaat) at Teluk Rasau Lake, Ogan Komering Ilir Regency, South Sumatra Province - Apriyanto, Ferly; Jubaedah, Dade; Herpandi, Herpandi (Program Pascasarjana Universitas Sriwijaya, 2024)
Abstract: Teluk Rasau lake is on of reserve area in South Sumatera, Indonesia. This research aims to analyze the suitability of the Teluk Rasau Lake fish reserve based on environmental, social, economic, and cultural aspects and provide management recommendations for fish reserve based on its suitability. The research implemented from August to September 2023 in 3 (three) locations using the purposive sampling method. The suitability through the approach analysis of the function and effectiveness of the fish reserve area, considering parameters such as water depth, water quality, availability of aquatic plants as riparian vegetation, protection, water area, spawning, feeding, and nursery grounds for fish, rare/protected species, legality aspects, ease of access, usage conflicts, and the role of the community supervisory groups. Each parameter was scored based on its importance for the fish reserve. The analysis results of the function and effectiveness of the fish reserve show that its feasibility is quite appropriate, with a score of 26, indicating that the fish sanctuary is moderately functional and fairly effective. It was concluded that these categories showed optimal performance for the conservation goals of protecting rare/endemic fish species and increasing fish stocks for the surrounding waters. However, community supervisory groups participation involving the role was still low. Co-management-based fish reserve management is a suitable approach for the Teluk Rasau Lake fish reserve.